Structural changes in the kidneys of experimental rats under conditions of administration of Vipera berus berus venom - Ahafonov , K.M. (Морфологія / Morphologia / Morfologìâ, 2026)
Background. Violation of the hemostasis system, the development of massive bleeding, myonecrosis, dermonecrosis, kidney dysfunction and other manifestations become the causes of disability or lethal consequences of viper bites. The kidneys are organs whose cells require a significant number of mitochondria to eliminate metabolic products from the blood and regulate fluid and electrolyte balance. Direct nephrotoxic or indirect hemolytic and rhabdomyolytic effects of viper venom components, activation of the OS phenomenon, which unfolds in several phases, cause irreversible kidney damage. Objective. Study of structural changes in the kidneys of experimental rats under conditions of administration of Vipera berus berus venom. Methods. Experimental studies were conducted on 20 male rats, which were intraperitoneally injected with a semi-lethal dose (LD50) (1.576 mg· g-1) of Vipera berus berus venom in saline. Kidney samples from animals of all groups were taken for microscopic examination. Histological preparations of the heart were stained with hematoxylin and eosin, and azan trichrome. Results and conclusion. Intoxication with the venom of the viper Vipera berus berus causes the developm ent of acute necrotic nephrosis, which is characterised by a combination of deep parenchymal dystrophy, destruction of the glomerular apparatus and massive hemorrhagic syndrome. The destruction of the histohematological barrier of the kidneys is noted. The venom causes enzymatic lysis of the basement membranes of the glomerular capillaries and Bowman’s capsule, and hydropic and granular dystrophy of the epithelium is observed. The vasotoxic effect of the venom manifests as multiple extravasations.